(untitled) (Research, Society and Development, 2022)
Students with high abilities, the focus of this research, are characterized by demonstrating a high potential in any of these areas, isolated or combined: intellectual, academic, leadership, psychomotricity, creativity and arts. The research is configured as a qualitative and quantitative research, taken as a unit. It aims characterize students with high abilities in Brazilian Higher Education by educational indicators of the Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira – INEP. The research was carried out by extracting data from the Higher Education Census conducted by INEP, in the period from 2017 to 2019, using the IBM SPSS Statistics® software, the variables analyzed were: high abilities, gender, race, administrative category and academic degree. After extracting the raw data, they were organized in Excel® tables and analyzed qualitatively and quantitatively based on thematic axes. According to the data revealed, we can trace a current profile of Higher Education Brazilian students with High Abilities, being mostly men, whites, studying in bachelor courses in private institutions. It is indicated the need for further studies and deepening with the educational indicators, in behalf of being a little explored area within the high abilities, as well as the realization of more studies with adults in the high abilities theme so that they somehow reverberate and reflect in positive actions for this portion of the population that has been neglected.